2019
DOI: 10.1186/s40101-019-0202-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of toe grip training on physical performance and cognitive function of nursing home residents

Abstract: Background Toe grip-related training requires individuals to actively exercise muscles that are not frequently used; therefore, it may improve not only toe grip strength but also cognitive function. The purpose of this study was to examine the effects of toe grip-related training on predictors of physical performance and cognitive function in nursing home residents. Methods A total of 35 nursing home residents (35 left and 35 right feet; mean age, 82.1 ± 7.9 years) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Studies have shown that progressive resistance training and toe-grip-related training, such as performing towelgathering exercises, are effective methods for improving the toe-grip strength [16,17]. However, if this training is not performed regularly, then it is difficult to maintain the beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that progressive resistance training and toe-grip-related training, such as performing towelgathering exercises, are effective methods for improving the toe-grip strength [16,17]. However, if this training is not performed regularly, then it is difficult to maintain the beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed an association between TFS and physical activity 2 , 3 ) , prevalence of diabetes mellitus in middle-aged men 8 ) , gait performance 4 ) , fall 5 , 6 , 7 ) , and cognitive function in the elderly 9 ) . TFS is a simple, safe, and inexpensive way to evaluate lower limb muscle strength.…”
Section: Discussionmentioning
confidence: 96%
“…Toe flexion is a combination of the action of plantar intrinsic and extrinsic muscles 1 ) . Toe flexor strength (TFS) is related to physical activity level 2 , 3 ) , locomotive performance 4 ) , fall 5 , 6 , 7 ) , diabetes mellitus 8 ) , and cognitive function 9 ) ; thus, evaluation of TFS may be useful for screening for health and aging-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Toe grip strength training in nursing home residents led to signi cant improvements in the fall risk index. A signi cant increase in TGS was noted in the intervention group compared to that in the non-intervention group [22]. Therefore, it is clinically important to evaluate and strengthen TGS to prevent falls in older adults.…”
mentioning
confidence: 98%
“…Toe grip strength training in nursing home residents led to signi cant improvements in the fall risk index. A signi cant increase in TGS was noted in the intervention group compared to that in the non-intervention group [22]. Therefore, it is clinically important to evaluate and strengthen TGS to prevent falls in older adults.To date, no study has investigated the relationship between falls and TGS in older adults with KOA who are at risk of falling owing to lower limb muscle weakness and impaired balance.…”
mentioning
confidence: 98%